2020
DOI: 10.1002/solr.202000119
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐Based Simple and Practical Dopant‐Free Hole‐Transporting Materials for Efficient Perovskite Solar Cells Using TiO2 Semiconductors

Abstract: A new series of structurally simple and easily accessible hole‐transporting materials (HTMs) YZT1–YZT4 using porphyrin backbone is devised for high‐performance perovskite solar cells (PSCs) with and without the aid of doping. The YZT‐series HTMs have either push–push or push–pull type planar linear molecular geometry with substitution of linear or branched alkylamine. UV–vis absorption, photoluminance (PL) quenching experiments, and theoretical studies all suggest a different pattern of molecular packing induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…8e) with simpler structures and easier preparation. 52 However, the PCE of batteries device used YZT-series as HTMs doped with tBP and FK209 is much lower than spiro-OMeTAD under the same condition (Table 3).…”
Section: Porphyrins As Hole-transport Materials In Perovskite Solar C...mentioning
confidence: 94%
“…8e) with simpler structures and easier preparation. 52 However, the PCE of batteries device used YZT-series as HTMs doped with tBP and FK209 is much lower than spiro-OMeTAD under the same condition (Table 3).…”
Section: Porphyrins As Hole-transport Materials In Perovskite Solar C...mentioning
confidence: 94%
“…Stability studies were carried out without dopants under the dark with RH 40% and showed that YZT4 retain 85% of the initial PCE after 340 h which is much better than that of spiro-OMeTAD. 87…”
Section: Porphyrins In Perovskite Solar Cellsmentioning
confidence: 99%
“…Efforts have been devoted to designing and fabricating HTMs from organic building blocks, [ 5,6 ] including organic small molecules, [ 7–36 ] polymers, [ 37,38 ] and organometallic compounds. [ 39–41 ] Among them small organic HTMs have received tremendous attentions due to their high performance, structural variety, and easy fabrication.…”
Section: Introductionmentioning
confidence: 99%